Mesoporous WO3 modified by Mo for enhancing reduction of CO2 to solar fuels under visible light and thermal conditions. Issue 172 (12th June 2016) - Wang, Lichao; Ha, Minh Ngoc; Liu, Zhifu; Zhao, Zhe
Abstract: Mesoporous WO3 (m-WO3 ) was synthesized by a hydrothermal method using mesoporous silica KIT-6 as a hard template and silicotungstic acid as a precursor.The m-WO3 modified by molybdenum (Mo) nanoparticles could be used as a stable catalyst for photo-thermal inducing CO2 reducting reactions for solar fuels. Under visible light irradiation (λ > 420 nm) and 250–, the catalytic activity of m-Mo/WO3 for the CH4 and CH3 OHevolution was found to be higher than that of m-WO3 and commercial WO3 . The amount of evolved CH3 OH from m-Mo/WO3 has reached 13.80 μmolg −1 in 1 2 h, which is ca.10 times as high as that of c-WO3 (1.36 μmolg −1 ) and 6.5 times as high as that of m-WO3 (2.12 μmolg −1 ), making it attractive for practical applications.